Harmful algal bloom species Microcystis aeruginosa releases thiamin antivitamins to suppress competitors - Mohammad Yazdani; Christopher P. Suffridge; Fangchen Liu; Cait M. Costello; Zhiyao Zhou; Gillian St. John; Ruchika Bhawal; Sheng Zhang; Geoffrey W. Coates; Mingming Wu; Beth A. Ahner (mBio)
ABSTRACT In environmental ecosystems, vitamin concentrations are often exceedingly low, and auxotrophy, or reliance on exogenous vitamins or vitamin precursors, is widespread. We show here that the widespread harmful algal bloom (HAB) species Microcystis aeruginosa, threatening freshwater aquatic ecosystems globally, releases a complex mixture of thiamin antivitamins, including bacimethrin and methoxythiamin, which induce thiamin deficiency in the model green alga Chlamydomonas reinhardtii. Putative biosynthetic genes for bacimethrin were upregulated in M. aeruginosa when grown in co-culture, resulting in a greater production of bacimethrin. Bacimethrin, methoxythiamin, oxidized forms of thiamin and methoxythiamin, and a novel structural homolog of bacimethrin were all found at elevated levels in the co-culture exometabolome extracts and were all inhibitory to the growth of C. reinhardtii individually at very low concentrations and as a mixture in culture medium extracts. The thiamin-requiring mutant C. reinhardtii, CC-25, was much more sensitive to bacimethrin and methoxythiamin than the wild-type. Thiamin addition largely rescued the inhibitory effects of exposure to antivitamins in both the wild-type and mutant strains. Finally, we determined that bacimethrin is present in aquatic environments and is elevated during Microcystis blooms. Thus, allelopathic suppression of competitors, particularly those that are auxotrophic for thiamin, by M. aeruginosa via the production of antivitamins in environments where thiamin availability is low, could help this species to become dominant and form blooms.IMPORTANCEThe frequent reliance of aquatic microorganisms on exogenous vitamins leaves them potentially vulnerable to antimetabolites that mimic vitamins. We show that Microcystis aeruginosa, a common freshwater harmful algal bloom (HAB) species, makes and releases a chemical that mimics the required vitamin thiamin (vitamin B1) and one of its precursors. In the laboratory, these chemicals, along with related ones, can harm other algae. Production of these chemicals may help Microcystis aeruginosa thrive under conditions where thiamin is scarce and forms toxic blooms. HABs threaten and kill fish and other aquatic animals, as well as contaminate drinking water. Discovery of a role for antivitamins in freshwater HAB formation could lead to new strategies to prevent or control HABs.